Psychometric properties of BREALD-30 for assessing adolescents' oral health literacy - Larissa Chaves Morais de Lima; Érick Tássio Barbosa Neves; Laio da Costa Dutra; Ramon Targino Firmino; Luiza Jordânia Serafim de Araújo; Saul Martins Paiva; Fernanda Morais Ferreira; Ana Flávia Granville-Garcia
ABSTRACT OBJECTIVE To evaluate the psychometric properties of the Brazilian Portuguese version of the Rapid Estimate of Adult Literacy in Dentistry (BREALD-30) administered to adolescents. METHODS The study included 750 adolescents: 375 aged 12 years and 375 aged 15-19 years, attending public and private schools in Campina Grande, state of Paraíba, Brazil, in 2017. Reliability was measured based on internal consistency and test-retest reliability. Convergent validity was measured based on correlations between BREALD-30 and Functional Literacy Indicator scores. Divergent validity was measured by comparing BREALD-30 scores with sociodemographic variables. For predictive validity, the association between BREALD-30 scores and the presence of cavitated carious lesions was tested using a multiple logistic regression model. All statistical tests were performed with a significance level of 5%. RESULTS BREALD-30 showed good internal consistency for the 12 year olds and 15 to19 year olds (Cronbach's alpha = 0.871 and 0.834, respectively) and good test-retest reliability [intraclass correlation coefficient (ICC) = 0.898 and 0.974; kappa = 0.804 and 0.808, respectively]. Moreover, item-total correlation was satisfactory for all items. BREALD-30 had convergent validity with the Functional Literacy Indicator for 12 year olds (rs = 0.558, p < 0.001) and for 15 to 19 year olds (rs = 0.652, p < 0.001). Participants with higher oral health literacy levels who attended private schools (p < 0.001), belonged to economic classes A and B2 (p < 0.001), and who had parents with higher education levels (p < 0.001) were included, indicating the divergent validity of the BREALD-30. Participants with lower BREALD-30 scores were more likely to have cavitated carious lesions [12 year olds: odds ratio (OR) = 2.37; 95% confidence interval (95%CI): 1.48-3.80; 15 to 19 year olds: OR = 1.96; 95%CI 1.24-3.11]. CONCLUSIONS BREALD-30 shows satisfactory psychometric properties for use on Brazilian adolescents and can be applied as a fast, simple, and reliable measure of oral health literacy.